Nutrition Education through the Study of Salted Fish Consumption: A Contextual Learning Resource for Hypertension Prevention - Jannah, St. Nurfatul; Hidayat, Rahmat; Rendi, Rendi; Masyhuri, Robertus; Wanci, Risman (Biology Teaching and Learning, 2025)
Abstract. This study aims to analyze the effect of health education on salted fish consumption in improving knowledge among patients with hypertension. The research used a pre-test and post-test design with 40 respondents selected through accidental sampling at Barombong Public Health Center, Makassar. Data analysis using the McNemar test showed a p-value of 0.000 (< α = 0.05), indicating a significant increase in knowledge after the educational intervention. A total of 21 respondents improved from poor to good knowledge. These findings suggest that nutrition education related to salted fish consumption can serve as an effective contextual learning resource for hypertension prevention. This locally relevant educational approach supports nurses’ roles in health promotion and can be developed into practical learning materials or media in community-based nursing care. Thus, the study reinforces the importance of contextual nutrition education in promotive and preventive health interventions.Keywords: health education, hypertension, salted fish, knowledge